Corrosion behavior of Shape Memory Alloy in NaCl environment and recovery maintenance in Cu-Zn-Al sysytem - Andrea Brotzu; Barbara De Filippo; Stefano Natali; Laura Zortea (Fracture and Structural Integrity)
Shape memory effect (SME) and the relation with corrosion behavior of Cu-Zn-Al Smart Memory Alloys (SMAs) were investigated using different techniques: Scanning Electron Microscopy equipped with an Energy Dispersive System, X-Ray Diffraction analysis, Electrochemical Test in NaCl solutions with different concentrations (0.035%, 0.35% and 3.5%), which simulate coastal conditions, mechanical characterization through tensile test and guided bend test.